Pengaruh Harga, Promosi, Dan Kualitas Produk Terhadap Keputusan Pembelian Pada E – Commerce Tiktok Shop (Studi Pada Mahasiswa Universitas Islam Malang) - Sujana, Ilham Alif; Rizal, Mohammad; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to test and explain the influence of price promotion and product quality on purchasing decisions. This study uses a quantitative approach which uses the maholtra formula to detemine the sample because the population is still not known for sure, seeing from the results of the maholtra dormula calculation the sample size is 80.This study uses a testing tool called spss. the test results on spss show that the t-test of the price promotion and product quality variables shows a value smaller than 0.05 so that it can be concluded that the price promotion and product quality variables have an effect on purchasing decisions and vice versa the f test also shows the same results of the price, promotion and product quality variables simultaneously affect purchasing decisions. Keywords : Price, Promotion, Product Quality, Purchasing Decisions.